PENGARUH PEMAHAMAN REGULASI, SISTEM INFORMASI, DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP MANAJEMEN ASET PADA SKPK KOTA LANGSA - Jefry Eka Prayogi Jefry; Iqlima Azhar; Muhammad Rizqi Zati (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2021)
Abstract This study aims to determine the effect of Regulatory Understanding, Information Systems and Competency of Human Resources on Asset Management in the City Work Unit (SKPK) of Langsa City. Data analysis was performed using SPSS (Statistical Package for Social Science) version 25.0. Data collection is done through primary data and secondary data. Determination of the sample used in this study is the census method with a total sample of 60 people. The equation model analyzed is multiple linear regression and hypothesis testing. The results of the study show that (1) Understanding of Regulations, Information Systems and Human Resource Competencies simultaneously affect asset management (2) Understanding of Regulations has an effect on Asset Management (3) Information systems have no effect on Asset Management (4) Competence of Human Resources has an effect on to Asset Management. Keywords : Regulatory Understanding, Information Systems, Human Resource Competence, Asset Management